AN ITERATIVE ALGORITHM OF OBJECT DETECTION IN VIDEO SEQUENCE BASED ON HISTOGRAM SPATIAL MEASURES - I. A. Baryskievic (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
A fast iterative algorithm of object detection in video sequence is proposed. It is based on local histogram properties and SPSO adaptation to image singularities. The parameters of algorithm are defined in terms of detection efficiency and computational complexity.